Leggere Anzaldúa con Foucault: Il Medesimo e l’Altro nelle Eterotopie delle Borderlands (Altre Modernità, 2018)
With Borderlands/La Frontera: The New Mestiza (1987), Gloria Anzaldúa offers a dramatic and revolutionary view on the life in the borderlands. Her ideas are still able to question the strictness of some cultural and political identities and the way they are used to reject diversity in the U.S.. And she does that by proving how diversity and complexity already characterize each and every identity in itself. Our aim was to re-read Anzaldúa in the light of what Michel Foucault proposed in Les Mots et Les Choses (1966) and in Des Espaces Autres (1967). We tried to interrogate Anzaldúa’s work starting from the principes chosen by the Foucault to identify hétérotopies. According to Foucault in fact, “the site is defined by relations of proximity between points or elements”. Then, how is identity built out of spatial relations? We applied Foucault’s principles to Anzaldúa’s work and to the American borderlands as a heterotopia within a heterotopia. We chose to consider both the border reality she denounces and the borderland conception she proposes.